(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Nowadays diesel power plants form the basis of distributed power generation in Russia, but they have disadvantages. The alternative variant is cogeneration plant based on the rotary-vane machine. One of the types of such machines is the rotary-vane external combustion vehicle (engine) developed in Pskov State University. Electrical subsystem of the plant requires its effective work to provide both start and generation modes. Development of such subsystem structure, employment of elements for links with other subsystems in the hierarchic control system is an actual task. The paper considers structures of the electrical part of the plant, simulation and experiment results.